Feeding Practices of Goat Farmers Under Field Conditions in Perambalur and Ariyalr District of Tamilnadu - P. Suresh Kumar (The Indian Veterinary Journal, 2023)
A field survey was conducted to document the existing feeding management practices followed by goats farmers in Perambalur and Ariyalur district of Tamil Nadu. The study was conducted from 240 farmers of 60 villages. The farmers were interviewed by using a pre- tested schedule and information was collected on the existing feeding practices through   interaction with the farmers and personal observations. The farmers were interviewed on the feeding management practices included grazing resources,  feeding of concentrate mixture 2-3 weeks  prior to breeding ,during late pregnancy and early lactation , feeding of colostrums and feeding of crop byproducts, silage, hay, cultivated fodder, mineral mixture and vitamin supplementation. .It was observed that community waste lands were the major grazing resources (50.88%) in the study area (Table.1) and all the farmers practiced grazing only on common lands on roadside bunks of tanks canals and forest areas. Significantly (P< 0.01) higher proportion of farmers of Perambalur district provided concentrate ration and crop by products to the goats during pregnancy than Ariyalur district. It was observed that only 22.08% of respondents provided concentrate during pregnancy and 20.80% percentage during lactation to does. Only 26.67% of goat farmers were providing crop byproducts. Most of the farmers of Ariyalur district practiced Migration of goat flocks ( 61.67% ) which was significantly higher than Perambalur district migration was practiced by 36.67% of respondents  during lean (summer) season. The farmers are not following concentrate mixture feeding even during the critical stages such as 2-3 weeks prior to breeding, late pregnancy and early lactation indicating that they need to be educated regarding scientific feeding practices to be followed by the   farmers need to be explained the importance of providing concentrate ration and mineral mixture and vitamins to the goats.